Multiple spatial frequency channels in human visual perceptual memory - Nemes, Vanda A. (2019)
No === Current models of short-term visual perceptual memory invoke mechanisms that are closely allied to low-level perceptual discrimination mechanisms. The purpose of this study was to investigate the extent to which human visual perceptual memory for spatial frequency is based upon multiple, spatially tuned channels similar to those found in the earliest stages of visual processing. To this end we measured how performance on a delayed spatial frequency discrimination paradigm was affected by the introduction of interfering or ‘memory masking’ stimuli of variable spatial frequency during the delay period. Masking stimuli were shown to induce shifts in the points of subjective equality (PSE) when their spatial frequencies were within a bandwidth of 1.2 octaves of the reference spatial frequency. When mask spatial frequencies differed by more than this value, there was no change in the PSE from baseline levels. This selective pattern of masking was observed for different spatial frequencies and demonstrates the existence of multiple, spatially tuned mechanisms in visual perceptual memory. Memory masking effects were also found to occur for horizontal separations of up to 6 deg between the masking and test stimuli and lacked any orientation selectivity. These findings add further support to the view that low-level sensory processing mechanisms form the basis for the retention of spatial frequency information in perceptual memory. However, the broad range of transfer of memory masking effects across spatial location and other dimensions indicates more long range, long duration interactions between spatial frequency channels that are likely to rely contributions from neural processes located in higher visual areas. === V.N. supported by a Ph.D. studentship funded by the Federation of Ophthalmic and Dispensing Opticians.